2005
DOI: 10.1021/nl050069a
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy of Single- and Double-Wall Carbon Nanotubes in Different Environments

Abstract: Individual single-wall carbon nanotubes (SWNTs) and double-wall carbon nanotubes (DWNTs) were suspended in water for optical studies using sodium-cholate and other surfactants. We used time-resolved photoluminescence (PL) spectroscopy to study the influence of tube chirality and diameter as well as of the environment on nonradiative decay in small diameter tubes. The studies provide evidence for PL from small diameter core tubes in DWNTs and for a correlation of nonradiative decay with tube diameter and excito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
217
2
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 205 publications
(228 citation statements)
references
References 22 publications
7
217
2
2
Order By: Relevance
“…While no literature data exists for ͑6,4͒ nanotubes at room temperature, the average lifetime of 14 ps is in general agreement with values reported for other nanotube chiralities. 17 The corresponding distribution established for ͑6,5͒ nanotubes within the same sample results in an average lifetime of 5 ps and a similar width. Remarkably, this value agrees very well with the 6 ps determined by pump-probe measurements for the same CoMoCat nanotube material allowing for a direct comparison of the results achieved by both techniques.…”
mentioning
confidence: 67%
“…While no literature data exists for ͑6,4͒ nanotubes at room temperature, the average lifetime of 14 ps is in general agreement with values reported for other nanotube chiralities. 17 The corresponding distribution established for ͑6,5͒ nanotubes within the same sample results in an average lifetime of 5 ps and a similar width. Remarkably, this value agrees very well with the 6 ps determined by pump-probe measurements for the same CoMoCat nanotube material allowing for a direct comparison of the results achieved by both techniques.…”
mentioning
confidence: 67%
“…Even though there are a few reports on PL studies of peapod-derived DWNTs ͑Ref. 17͒ and catalytically grown DWNTs, 18,19 those studies are quite different from ours because we used highly pure crystalline DWNTs ͑Ref. 14͒ to eliminate the effect of impurities ͑i.e., unwanted SWNTs, amorphous carbon, and metallic impurities͒.…”
mentioning
confidence: 83%
“…It has been reported that the inner tubes of CVD-grown DWCNTs with small diameter are preferred over SWCNTs for producing photo-luminescent materials [26,27]. Due to their coaxial structure, the inner tubes of DWCNTs are expected to possess higher structural perfection and to be more resistant towards environmental changes when compared to SWCNTs.…”
Section: Thermal Stability Of Dwcntsmentioning
confidence: 99%